Islamic Literature Discourse in the Postcolonial Era: The Transcendental Literature of Indonesia and Genuine Literature of Malaysia (Malay Literature, 2012)
This article discusses the idea of Prophetic Literature or Sufi Literature that developed along the same lines as Transcendental Literature, founded by Kuntowijoyo. The core philosophies behind Transcendental Literature are the teachings of Sufism and mysticism. With Islam Kejawen (Javanese Sufism) as a background, Transcendental Literature emphasizes the spiritual experience and effort by humans to seek the love of Allah. It also emphasizes on traditional elements such as the "return to the roots of local culture", including Kejawen (Javanese Sufism) as a source to respond to the post-colonial literary discourse. In comparison, in Malaysia, Genuine Literature, pioneered by Mohd. Affandi Hassan, attempts to differentiate between the term and concept of kesusasteraan (literature), which is linked to Western fiction, and persuratan (writing), Mohd. Affandi Hassan's ambitious venture was to liberate Muslim authors from Western colonization. Genuine (Islamic) Literature focuses on 'ilm or knowledge, hence excluding aspects of superstition and imagination in literary works. Also, in Genuine Literature, the real beauty in literary works lies in the "combination of aesthetics and intellect". Genuine Literature also rejects absolute freedom for authors, with creativity no longer taken to be a measure of creativity. As an early discussion, this paper will highlight aspects of the Transcendental Literature of Indonesia and Genuine Literature of Malaysia and how they were presented as a response to the Western discourse. Both clearly try to provide "Islamic Literature" with distinctive features to create a more meaningful post-colonial discourse.Keywords: Islamic Literature, Transcendental Literature, Genuine Literature, Javanese Sufism, Post Colonial Literature